Physician-patient communication in the prevention of female reproductive tract infections: some limitations - Makuch María Y.; Botega Neury José; Bahamondes Luis (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
The objective of this study was to describe the information that women with tubal infertility recalled having received from physicians when they consulted for a reproductive tract infection (RTI) and the information physicians reported having provided to women consulting for RTIs. Interviews were conducted with 16 women presenting primary tubal infertility selected on the basis of purposeful sampling criteria. Also, 15 physicians working in the public health network in the city of Campinas, Brazil, were selected at random and interviewed. Analysis of the women's statements concerning previous RTI-related medical consultations showed that they did not recall having received any information on either prevention or the impact of RTI on their reproductive future. Analysis of interviews with physicians showed that the information they provided to women consulting for RTIs was incomplete and unclear. The information women recalled having received and that which physicians remembered having provided at the time of treating a patient with RTI was similar. In conclusion, these women lacked adequate or complete information and that it was probably not possible for them to adopt measures to avoid repetition of RTI and minimize risk of tubal infertility.